Sejarah Penafsiran Ajaran Paulus Mengenai Pembenaran Oleh Iman - Warseto Freddy Sihombing (Institut Agama Kristen Negeri Tarutung, 2020)
AbstractNo one can be justified before God for doing good deeds. No matter how good a man is, if he does not believe in Jesus Christ, the Son of God, he will not be saved from the wrath of God to come. There is no human being who is right before God, and no sinful man can save himself in any way. The only way out is in the way that God has given to the problem of all sinners, by sending Jesus Christ to the world to die for sinners.